177Lu-doxycycline as potential radiopharmaceutical: electrochemical characterization, radiolabeling, and biodistribution in tumor-bearing mice. (2nd December 2021) - Milanović, Zorana; Janković, Drina; Vranješ-Đurić, Sanja; Radović, Magdalena; Prijović, Željko; Zavišić, Gordana; Perić, Marko; Stanković, Dalibor; Mirković, Marija
Abstract: Purpose: Recent studies with doxycycline as adjuvant therapy to conventional chemotherapy have shown promising results in cancer therapy. The current study aimed to examine the capability of 177 Lu-labeled tetracycline ligand, doxycycline hyclate, to use as an anticancer agent. Materials and methods: Doxycycline was radiolabeled with beta-emitting radioisotope 177 Lu. Complex formation and its interaction with DNA were investigated electrochemically. Binding of 177 Lu-doxycycline to CT 26 cell line was done. Biodistribution of 177 Lu-doxycycline was examined in healthy Wistar rats and CT26 colon carcinoma tumor-bearing mice by i.v. and i.p. administration, respectively. Results: Doxycycline hyclate was successfully radiolabeled with 177 Lu in high radiolabeling yield (>99%). The radiolabeled complex was stable in vitro in saline and human serum over 72 h. Non-radioactive Lu-doxycycline complex formation was demonstrated electrochemically as well. Intercalative interactions of the doxycycline and Lu-doxycycline with DNA were proved using simultaneously spectrophotometric and electrochemical methods. The binding of the radiolabeled complex with plasma proteins was 4.0 ± 0.4%. The partition coefficient showed the lipophilic nature of the complex similar to the free ligand. The binding curve demonstrates binding from 0.1 nM concentrations of 177 Lu-doxycycline, with half-binding estimated ∼100 nM. Biodistribution studies of 177 Lu-doxycycline in CT26 colon tumor-bearing mice showed a satisfactory accumulation rate in the tumor (2.88 ± 0.85% ID/g) 3 h after intraperitoneal injection. Both the hepatobiliary system and the urinary system were prominent as excretory routes of the radiolabeled complex. Conclusion: Considering obtained results, 177 Lu-doxycycline complex, due to its excellent electrochemical and biological characteristics, with emphasis on the binding ability to DNA via intercalative interaction as well as significant accumulation in the tumor, is suitable for further in vivo studies to investigate its potential use in cancer treatment.